Simulation Study of a Futsal Ball Deformation in Normal Impact Using Finite Element Method - Fabian Halley Pata, Alban Dattu; Syed Tarmizi, Syed Shazali; Magdalene, Andrew Munot; Abang Mohamad Aizuddin, Abang Mohd Mohtar; Noor Hisyam, Noor Mohamed (IACSIT Press,University Politehnica of Bucharest, Romania, 2018)
—The popularity of the futsal games has gradually increased since it was introduced in Uruguay. Since that, the futsal games became a medium for the young players to train to be professional footballers. Many coaches are avoiding heading tactic until they are 12 years of age. This technique can lead into the potential cause of traumatic brain injury. To date there has been no study to predict the deformation of the futsal ball in normal impact on flat surface at low speeds. The purpose of this study is to investigate the deformation behavior of the futsal ball upon impact. The free fall drop test is performed on the futsal ball size 4 when hitting a rigid target at different heights 500mm, 1,000mm, and 1,500mm. The result shows that, the higher ball drop, the higher deformation of the ball. Then, a finite element model (FEM) of a futsal ball was constructed and the simulation of the ball analysis was done by comparison between two materials, which were Butyl Rubber (IIR) and Latex Rubber (NR). The results show that, the Butyl Rubber is the better material for futsal ball construction, as there are less deformation and stress which is in allowable stress. However, further improvement needs to be done by taking into consideration of the futsal ball under large deformation as well as at a high impact.